Effect of Chinese Herbal Fumigation Combined with Tuina on Vertigo and Concentrations of Endothelin and Calcitonin Gene-related Peptide in Patients with Vertebral Artery Cervical Spondylosis - Zhao, Cheng-fei; Liu, Xiao-an; Ding, Yun (Journal of acupuncture and tuina science, 2014)
Objective： To observe the effect of Chinese herbal fumisation combined with three-step tuina manipulation on concentration of endothelin （ET） and calcitonin gene-related peptide （CGRP） and vertigo in patients with vertebral artery cervical spondylosis （VACS）. Methods： A total of 120 eligible cases were randomly allocated into an observation group and a control group, 60 in each group. Cases in the observation group were treated with Chinese herbal fumigation combined with three-step tuina manipulation, whereas cases in the control group were treated with oral Flunarizine Hydrochloride Capsules. Results： After treatment, vertigo in both groups was alleviated; there were intra-group significant differences in ET decrease and CGRP increase （P〈0.01, P〈0.05）; and there were also inter-group significant differences （both P〈0.05）. Conclusion： Chinese herbal fumigation combined with three-step tuina manipulation can regulate the levels of ET and CGRP and improve vertigo in patients with VACS. Its therapeutic efficacy is superior to oral Flunarizine Hydrochloride Capsules.